Vispro improves imaging analysis for Visium spatial transcriptomics - Huifang Ma; Xingyuan Zhang; Yilong Qu; Anru R. Zhang; Zhicheng Ji (Genome Biology)
Abstract Spatial transcriptomics enables spatially resolved gene expression analysis, but accompanying histology images are often degraded by fiducial markers and background regions, hindering interpretation. To address this, we introduce Vispro, an end-to-end automated image processing tool optimized for 10× Visium data. Vispro includes modules for fiducial marker detection, image restoration, tissue region detection, and segmentation of disconnected tissue areas. By enhancing image quality, Vispro improves the accuracy and performance of downstream analyses, including tissue and cell segmentation, image registration, gene expression imputation guided by histological context, and spatial domain detection.